Enhancing hospitality business visibility through strategic search engine optimization (SEO) implementation in digital marketing platforms - Suwitri, Sang Ayu Nyoman; Gede, I Gusti Ketut; Wajdi, Majid (Journal of Commerce, Management, and Tourism Studies, 2025)
This study aims to analyze the implementation of Search Engine Optimization (SEO) as part of digital marketing strategies to enhance online visibility in the hospitality industry. In response to rapid developments in digital technology, hospitality businesses are required to adapt to modern marketing practices that are more measurable and customer-oriented. One of the key strategies in this transformation is SEO, which plays a pivotal role in improving website rankings on search engine result pages, thereby attracting potential customers organically. This research employs a qualitative approach using data collection methods such as direct observation, in-depth interviews, and documentation. Data sources include digital marketing personnel, analytics dashboards, and supporting literature. The primary focus is on evaluating how SEO initiatives—such as keyword optimization, content enrichment, and structural enhancements—contribute to measurable performance improvements. Findings indicate that the implementation of SEO, which began in December 2023, had a significant positive impact. The number of unique visitors increased by 68%, total visits grew by 101%, and page views surged by more than 624% in 2024 compared to the previous year. These improvements are closely linked to the systematic application of SEO techniques, including content relevancy, keyword alignment, and the use of analytical tools such as Google Analytics for ongoing evaluation. The conclusion drawn from this study is that consistent and well-executed SEO implementation significantly enhances online visibility and strengthens competitiveness in the digital hospitality landscape. The study emphasizes the importance of maintaining continuity in SEO practices to ensure long-term benefits. It also serves as a reference for digital marketing practitioners seeking to optimize their web presence in a highly competitive market.